Team teaching in undergraduate nursing programs: A scoping review. Issue 3 (June 2022) - Pathrose, Sheeja Perumbil; Raeburn, Toby; Sanchez, Paula; Elmir, Hind; Alomari, Albara; Ogunsiji, Olayide
Abstract: Aim: To explore studies related to team teaching in undergraduate nursing education and to identify its implications for practice. Background: Team teaching is a pedagogical approach that has been used in a wide variety of settings since the mid-twentieth century. This approach aims to encourage critical thinking through exposure to a multifocal teaching approach. Incorporating various teaching approaches is crucial to cultivating knowledge and practical ability among future nurses. Despite its apparent potential as a pedagogy, peer-reviewed literature contains little evidence regarding the implementation of team teaching in undergraduate nursing education. Design: Scoping review strategy was used in this review to examine the extent and range of available literature on team teaching in undergraduate nursing education. Methods: : The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist was used as the reporting guideline for this review. Literature search was conducted using six databases in addition to grey literature search. Results: Six papers met the inclusion criteria, and all were conducted in high income countries. Four main themes were evident in included studies. These were study approach, student perspectives, teacher perspectives and broad recommendations. The majority (96%) of participants in the studies were students. Positive findings revealed that team teaching is of benefit to students' active learning, reflection skills, leadership skills, and student-teacher bonding. Team teaching that pairs academics with frontline clinicians was also suggested as one way to address the gap between theory and practice often cited as a weakness of modern-day nursing training. Challenges identified by studies included, students' experiences observing personality clashes between teachers, and extra time demands being placed on teachers due to intensive planning. Conclusions: This review highlights that any level of teaming and/or collaboration is better, in many aspects, than solo teaching in undergraduate nursing education. A clear need was identified for research exploring the perspective of nurse educators and managers regarding their perceptions of team teaching.